The Differences of Adaptive and Maladaptive Coping Mechanisms on the Intensity of Maternal Pain in the First Stage of Labor - Shofia Maharani Khoirun Nisa; Wiwik Agustina (The Avicenna Medical Journal, 2024)
Background: Coping mechanisms play a crucial role in managing maternal pain during labor. Understanding the differences between adaptive and maladaptive coping strategies can help improve maternal care and pain management. The aim of this study was to determine the differences in the level of coping mechanisms and the intensity of pain in mothers during the first stage of labor. Methods: A cross-sectional study was conducted on 66 laboring mothers at PKU Muhammadiyah Delanggu Hospital. The intensity of pain was measured using the Visual Analog Scale (VAS), while coping mechanisms were assessed using the Brief COPE Questionnaire. Data analysis was performed using the Wilcoxon test with a significance level of p < 0.005. The results of the Wilcoxon test indicate a significant difference between adaptive and maladaptive coping mechanisms in relation to labor pain intensity (p < 0.005) (CI=95%). Among mothers with mild pain, 76.2% used adaptive coping mechanisms, whereas only 23.8% relied on maladaptive strategies. Similarly, in the moderate pain group, 78.8% used adaptive coping, while 21.2% used maladaptive coping. However, in the severe pain category, the majority (66.7%) used maladaptive coping mechanisms, whereas only 33.3% applied adaptive coping strategies. Results: The study confirms that adaptive coping mechanisms are associated with lower pain intensity during labor, while maladaptive strategies correlate with higher pain levels. Conclusion: These findings highlight the need for healthcare providers to educate and encourage expectant mothers to adopt effective coping strategies to improve maternal comfort and childbirth outcomes. Future research should explore interventions that enhance adaptive coping mechanisms in labor management.